Histological, Histochemical and Ultrastructural Study of Thyroid Gland in Mature Male Indigenous Rabbit (Oryctolagus Cuniculus) - ahmed, sawsan; Hadaf H. Mohammed (University of Thi-Qar Journal of agricultural research, 2025)
This current study was designed to investigate the histological, histochemical structure and ultrastructural study of thyroid gland in mature male rabbits (Oryctolagus Cuniculus). Ten healthy mature male rabbits (six months in age) were used divided into two groups, each of which contains 5 male rabbits. The first group was used to histological and histochemical study of thyroid gland, while the second group was used to ultrastructural study, The histological study included the general histological structure description. Ultrastructural study included the knowing the microscopic structures that distinguish the different secretory cells found in the thyroid gland in mature male rabbits. The histochemical results shown thyroid follicles colloids of animal were showed positive reaction for PAS and alcian blue (PH 2.5) stains. Ultrastructural results showed the cytoplasm of follicular cells presented mitochondria in diverse shapes. The rough endoplasmic reticulum appeared as extensive elongated and irregular elliptical cisterns. The findings from this study contribute to a better understanding for deep details of thyroid gland in domestic animal.